2021
DOI: 10.1371/journal.pone.0246326
|View full text |Cite
|
Sign up to set email alerts
|

The differential impact of pediatric COVID-19 between high-income countries and low- and middle-income countries: A systematic review of fatality and ICU admission in children worldwide

Abstract: Background The overall global impact of COVID-19 in children and regional variability in pediatric outcomes are presently unknown. Methods To evaluate the magnitude of global COVID-19 death and intensive care unit (ICU) admission in children aged 0–19 years, a systematic review was conducted for articles and national reports as of December 7, 2020. This systematic review is registered with PROSPERO (registration number: CRD42020179696). Results We reviewed 16,027 articles as well as 225 national reports fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 19 publications
6
125
0
16
Order By: Relevance
“…LMICs or the respiratory disease more commonly seen in young children. There has been more attention on MIS-C, a novel condition but one associated with very low mortality, rather than the COVID-19 related illnesses that we and others have found to have higher mortality 12 . This higher mortality warrants further investigation to determine whether care and outcomes can be improved, particularly in resource-limited settings.…”
Section: Current Literature Has Not Sufficiently Evaluated the Impact Of Critical Pediatric Covid-19 Inmentioning
confidence: 77%
See 1 more Smart Citation
“…LMICs or the respiratory disease more commonly seen in young children. There has been more attention on MIS-C, a novel condition but one associated with very low mortality, rather than the COVID-19 related illnesses that we and others have found to have higher mortality 12 . This higher mortality warrants further investigation to determine whether care and outcomes can be improved, particularly in resource-limited settings.…”
Section: Current Literature Has Not Sufficiently Evaluated the Impact Of Critical Pediatric Covid-19 Inmentioning
confidence: 77%
“…While pediatric COVID-19 mortality rates are low in HICs, they are more concerning in LMICs. The review by Kitano and colleagues found that over 90% of pediatric COVID-19 deaths were from LMICs and that mortality risk was highest in children under 1 year old 12 . Mortality differences in LMICs can be partly explained by less-developed healthcare infrastructure and lack of resources, but the reasons for age-related differences are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of children who died without ICU support was about 36% in the poorest regions (Northeast and North), compared with about 23% in the richest regions (Southeast and South). Notably, in the systematic review reported by Kitano and colleagues, 8 among 138 countries, Brazil had the highest rate of deaths in the young population, reaching about 23•6 per 1 000 000 children. Consequently, the high mortality observed in our sample is likely to reflect both the inclusion of hospitalised individuals at the more severe end of the spectrum and an apparent inability to provide the highest level of care to the most critically ill patients, especially in less developed regions.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 In addition, a systematic review has highlighted a greater impact of paediatric COVID-19 fatality in low-income and middle-income countries compared with high-income countries. 8 To date, however, few paediatric cohort studies have directly investigated the risk factors associated with severe COVID-19. 9 Further understanding these issues in children could provide important insights and guide the development of therapeutic and vaccination strategies for target groups.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis indicated that the outcome of children admitted to hospital with acute COVID-19 is worse in LMICs than in HICs (case fatality rates 0·29% [95% CI 0·28–0·31%] vs 0·03% [0·03–0·03%]). 14 Vaccinating CYP in LMICs may ultimately have more benefit to their health status compared with CYP in HICs.…”
mentioning
confidence: 99%